Polydopamine Functionalized Graphene Oxide as Membrane Nanofiller: Spectral and Structural Studies - Abedalkader Alkhouzaam (15842647) (2021)
High-degree functionalization of graphene oxide (GO) nanoparticles (NPs) using polydopamine (PDA) was conducted to produce polydopamine functionalized graphene oxide nanoparticles (GO-PDA NPs). Aiming to explore their potential use as nanofiller in membrane separation processes, the spectral and structural properties of GO-PDA NPs were comprehensively analyzed. GO NPs were first prepared by the oxidation of graphite via a modified Hummers method. The obtained GO NPs were then functionalized with PDA using a GO:PDA ratio of 1:2 to obtain highly aminated GO NPs. The structural change was evaluated using XRD, FTIR-UATR, Raman spectroscopy, SEM and TEM. Several bands have emerged in the FTIR spectra of GO-PDA attributed to the amine groups of PDA confirming the high functionalization degree of GO NPs. Raman spectra and XRD patterns showed different crystalline structures and defects and higher interlayer spacing of GO-PDA. The change in elemental compositions was confirmed by XPS and CHNSO elemental analysis and showed an emerging N 1s core-level in the GO-PDA survey spectra corresponding to the amine groups of PDA. GO-PDA NPs showed better dispersibility in polar and nonpolar solvents expanding their potential utilization for different purposes. Furthermore, GO and GO-PDA-coated membranes were prepared via pressure-assisted self-assembly technique (PAS) using low concentrations of NPs (1 wt. %). Contact angle measurements showed excellent hydrophilic properties of GO-PDA with an average contact angle of (27.8°). Other Information Published in: Membranes License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/membranes11020086